2019
DOI: 10.21873/invivo.11796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ESM-1 Gene Expression on Outcomes in Stage II/III Gastric Cancer Patients Who Received Adjuvant S-1 Chemotherapy

Abstract: Background/Aim: Endothelial cell-specific molecule-1 (ESM-1) is a soluble proteoglycan which has important role in various biological events. We investigated the impact of the ESM-1 expression in cancer tissues on outcomes in stage II/III gastric cancer patients who received adjuvant S-1 chemotherapy. Patients and Methods: The ESM-1 mRNA expression in cancerous tissues and adjacent normal mucosa from 253 patients was measured. The associations between the ESM-1 gene expression and the survival and clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…ESM1 is highly expressed in vascular endothelial cells, i.e., epithelial cells of the distal renal tubules, bronchial tubes, and submucosal lung glands in normal tissues [ 22 ]. ESM1 expression is also upregulated in lung cancer [ 23 ], gastric cancer [ 24 ], breast cancer [ 25 ], bladder cancer [ 26 ], and other malignant tumors and is associated with the inflammatory response and tumor progression. Moreover, ESM1 participates in tumor growth, migration, invasion, and angiogenesis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESM1 is highly expressed in vascular endothelial cells, i.e., epithelial cells of the distal renal tubules, bronchial tubes, and submucosal lung glands in normal tissues [ 22 ]. ESM1 expression is also upregulated in lung cancer [ 23 ], gastric cancer [ 24 ], breast cancer [ 25 ], bladder cancer [ 26 ], and other malignant tumors and is associated with the inflammatory response and tumor progression. Moreover, ESM1 participates in tumor growth, migration, invasion, and angiogenesis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that ESM1 is expressed in multiple tissues, including the kidney, liver, thyroid gland, skin, and gastrointestinal tract [14][15][16]. Moreover, aberrant ESM1 expression is associated with multiple diseases, including inflammation [17], vascular disorders [18], and cancer [19].ESM1 is upregulated in a broad spectrum of cancers, often correlated with a poor prognosis [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ESM1 can be used as a prognostic marker in triple-negative breast cancer ( 21 , 26 ). It may be that ESM1 promotes tumor invasion and migration by regulating tumor angiogenesis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%